Otwarte fundusze emerytalne : porównanie i projekcja pozycji na rynku ubezpieczeń emerytalnych - Miszczyńska, Dorota (Open Pensions Funds (OPF) - Comparison and Forecast Position on the Insurance Market, 2006)
The paper proposes an application of the methodology of multicriterial optimization to forecast the ranking of OPF between 2005 and 2006. The analysis starts with a historical ranking of the Polish Opened-end Pension Founds (OPF) based on 8 criteria, done by discreet multicriterial optimization method Promethee. Then we forecast the criteria, based on structure indicators. We discuss several variants of a multistage forecasting procedure for the criteria, up to bipropotional RAS method. Finally the discreet multicriterial optimization methods are being used to rank the future performance of OPF between 2005 and 2006 on the basis of the forecasted values of criteria.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 293-305